The degree of availability of higher order thinking skills in science textbook for the fourth grade in the Syrian Arab Republic (Journal of Hama University, 2026)
The current research aims to identify the higher-order thinking skills that should be available in the science book for the fourth grade, as prescribed by the Ministry of Education in the Syrian Arab Republic, and to identify the degree of availability of higher-order thinking skills (observation, problem solving, analysis, application) in the science book. To achieve these objectives, the descriptive-analytical approach was followed, using a list of higher-order thinking skills and a content analysis form. The list of higher-order thinking skills included (4) main skills (observation, problem solving, analysis, application), which included (14) sub-indicators. The scientific boundaries are the aforementioned higher-order thinking skills, and the time boundaries are the second semester of the academic year (2024-2025), while the sample is represented by the science book.The researcher reached a set of results, the most important of which are: the existence of a weakness in the high-order thinking skills of the fourth grade, as they all came in a weak availability degree as determined by the current research (from 20% to less than 40%), and the observation skill came in first place, the analysis skill came in second place, the problem-solving skill came in third place, and the application skill came in fourth and last place. In light of the results, the research presented a set of proposals, the most important of which are: directing the authors of science books for the first phase of the basic education stage to the necessity of reviewing the high-order thinking skills and including them within the content, exercises, and questions.